Effect of residence times on river Mondego estuary eutrophication vulnerability - Duarte, António A. L. S. (2001)
The south arm of Mondego estuary, located in the central western Atlantic coast of Portugal, is almost silted up in the upstream area. So, the water circulation is mostly driven by tides and the tributary river Pranto discharges. Eutrophication has been taking place in this ecosystem during last twelve years, where macroalgae reach a luxuriant development covering a significant area of the intertidal muddy flat. A sampling program was carried out from June 1993 to June 1994. Available data on salinity profiles and on nutrients loading into the estuary south arm are being used in order to get a better understanding of the ongoing changes. River Pranto flow discharges, controlled by a sluice, were also monitored. Integral formulations are typically based on assumptions of steady-state and well mixed systems and thus cannot take into account the space and time variability of estuarine residence times, due to river discharge flow, tidal coefficients, discharge(s) location and time of release during the tidal cycle. This work presents the hydrodynamics modelling (2D-H) of this system in order to estimate the residence times variability and to assess their effect on the estuarine eutrophication vulnerability, contributing for proper environmental management strategies selection